2001
DOI: 10.1177/01461672012712009
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Commitment and Reciprocity in a Real-Time Public Goods Game

Abstract: Allowing players in public goods games to make small incremental commitments to contributing to the good might facilitate cooperation because it helps to prevent players from being “free ridden,” contributing more to the public good than other group members. Two experiments using a real-time version of the voluntary contribution mechanism were conducted to investigate the hypothesis that players are generally willing to contribute public goods conditional on beliefs that others are doing so at similar levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
77
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 46 publications
16
77
1
1
Order By: Relevance
“…Clearly, the notion of type must be understood with respect to a particular class of decisions; if cooperation is very costly, we presume universal defection would obtain (21). Nonetheless, our results add to the growing body of research that suggests that reciprocity is an important motive in group contexts across a range of institutional arrangements (45,46). Additional work will be required to determine the conditions under which players separate into types, including conditional cooperative ones, and which institutions have the effect of homogenizing play.…”
Section: Discussionmentioning
confidence: 65%
“…Clearly, the notion of type must be understood with respect to a particular class of decisions; if cooperation is very costly, we presume universal defection would obtain (21). Nonetheless, our results add to the growing body of research that suggests that reciprocity is an important motive in group contexts across a range of institutional arrangements (45,46). Additional work will be required to determine the conditions under which players separate into types, including conditional cooperative ones, and which institutions have the effect of homogenizing play.…”
Section: Discussionmentioning
confidence: 65%
“…they cooperate more when they perceive that co-players are more willing to cooperate Dawes, 1991, 1993;Ledyard, 1995;Fischbacher et al, 2001;Lubell and Scholz, 2001), and less when they believe that co-players are free riding (Fehr and Gächter, 2000;Kurzban et al, 2001a).…”
Section: Opening Cooperative Moves and Subsequent Monitoring Forms Inmentioning
confidence: 99%
“…More seriously, sufficient penetration by free riding can trigger the termination of an otherwise mutually beneficial ongoing intercontingent effort. Consequently, unless maintained by corrective social feedback, cheating or undercontribution will spread contagiously, and contributions to joint efforts will ratchet downwards (Kurzban et al, 2001a). When opportunities for monitoring and feedback are inadequate, effort minimization tends to operate unopposed, and the cooperative network erodes away.…”
Section: Opening Cooperative Moves and Subsequent Monitoring Forms Inmentioning
confidence: 99%
“…Our results should therefore help us to understand the development of cooperative relationships. They may also be compared with analogous results from studies of contributions to public goods, where it has been suggested that incremental strategies of commitment may increase the production of public goods in later rounds (Kurzban et al 2001). The prediction that reciprocal relationships will develop from small beginnings is also consistent with the observation of Axelrod (1984) that in the 'live-and-let-live' system of trench warfare 'restraint undertaken in certain hours could be extended to longer hours'.…”
Section: Discussionmentioning
confidence: 66%